2017
DOI: 10.1002/jssc.201700048
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic stationary phases with a longitudinal gradient of porosity

Abstract: The duration of the hypercrosslinking reaction has been used to control the extent of small pores formation in polymer-based monolithic stationary phases. Segments of five columns hypercrosslinked for 30-360 min were coupled via zero-volume unions to prepare columns with segmented porosity gradients. The steepness of the porosity gradient affected column efficiency, mass transfer resistance, and separation of both small-molecule alkylbenzenes and high-molar-mass polystyrene standards. In addition, the segmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is noteworthy that subtle change of pore structure including pore size, pore size distribution (PSD), and pore size uniformity particularly influences the separation of macromolecules . Recently, a series of researches about the influence of pore structure on protein capacity , column efficiency , reproducibility , etc. had been carried out widely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that subtle change of pore structure including pore size, pore size distribution (PSD), and pore size uniformity particularly influences the separation of macromolecules . Recently, a series of researches about the influence of pore structure on protein capacity , column efficiency , reproducibility , etc. had been carried out widely.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that subtle change of pore structure including pore size, pore size distribution (PSD), and pore size uniformity particularly influences the separation of macromolecules [3,4]. Recently, a series of researches about the influence of pore structure on protein capacity [5], column efficiency [6], reproducibility [7], etc. had been carried out Abbreviations: AFM, atomic force microscopy; LF, low field; PSD, pore size distribution; SEC, size exclusion chromatography Conflict of interest: We declare that we do not have any commercial or associative interest that represents a conflict of interest in connection with the work submitted.…”
Section: Introductionmentioning
confidence: 99%
“…They found that columns with a shallow porosity gradient produced comparable sizeexclusion separation of polystyrene standards but had a higher permeability compared to a completely hyper-crosslinked column. (123)…”
Section: Applications Of Polymer and Silica Monolithic Columnsmentioning
confidence: 99%
“…Up to 83 000 plates/m were obtained for benzene in the separation of a mixture of alkylbenzenes with a hypercrosslinked monolith using 1,6‐dichlorohexane as solvent, AlCl 3 as catalyst, and a temperature of 75°C for 2 h for hypercrosslinking . The separation capabilities of hypercrosslinked monolith stationary phases were also evaluated by preparing segments of five columns using different reaction times (30–360 min) . The hypercrosslinked monolith segments were coupled via zero‐volume unions, creating stationary phases with porosity gradients.…”
Section: Hypercrosslinkingmentioning
confidence: 99%